A Phase 1 study of the long‐acting anti‐IL‐5 monoclonal antibody GSK3511294 in patients with asthma. Issue 2 (24th August 2021) - Singh, Dave; Fuhr, Rainard; Bird, Nicholas P.; Mole, Sarah; Hardes, Kelly; Man, Yau Lun; Cahn, Anthony; Yancey, Steven W.; Pouliquen, Isabelle J.
Abstract : Aims: GSK3511294 is a humanized anti‐interleukin (IL)‐5 monoclonal antibody (mAb) engineered for extended half‐life and improved IL‐5 affinity versus other anti‐IL‐5 mAbs. This study examined its safety, tolerability, pharmacokinetics (PK) and effect on blood eosinophil counts. Methods: This was a double‐blind, parallel‐group, single‐ascending‐dose, multicenter, Phase 1 study (205 722;NCT03287310) in patients with asthma and a blood eosinophil count ≥200 cells μL −1 . Patients were randomized 3:1 within dose cohorts to receive a single subcutaneous dose of GSK3511294 (2, 10, 30, 100 or 300 mg) or placebo and followed for up to 40 weeks to assess safety (primary endpoint), ratio to baseline in blood eosinophil count, plasma PK parameters and frequency/titers of binding antidrug antibodies (all secondary). Results: Forty‐eight patients received the study drug and completed the study. Adverse events (AEs) occurred in 92% of placebo‐treated and 81% of GSK3511294‐treated patients. There were no AEs leading to study withdrawal or serious AEs; hypersensitivity (one event in one patient) and injection‐site reaction (three events in two patients) occurred infrequently. Marked reductions (>48%) in blood eosinophil count were seen from 24 hours post‐dose with all GSK3511294 doses but not placebo; suppression was maintained for longer with increasing dose (82% and 83% adjusted reductions vs placebo with 100 and 300 mg, respectively, at week 26). PK were linear and dose proportional over the dose range; terminal half‐life was 38‐53 days. Conclusions: GSK3511294 was well tolerated, with linear and dose proportional PK, extended half‐life and blood eosinophil count reduction, supporting less frequent dosing versus other anti‐IL‐5 mAbs. Abstract :